2015
DOI: 10.1021/acs.est.5b03782
|View full text |Cite
|
Sign up to set email alerts
|

New Antimicrobially Amended Media for Improved Nonpoint Source Bacterial Pollution Treatment

Abstract: Nonpoint source pollution (NPS) such as stormwater runoff may introduce high loads of bacteria, impairing surface water bodies. The existing filter materials in stormwater best management practices (BMP) are typically not designed to inactivate bacteria. Herein, novel filtration media were extensively tested for microbial load reduction in stormwater runoff. Red cedar wood chips (RC) were amended with different loadings of either 3-(trihydroxysilyl) propyldimethyloctadecyl ammonium chloride (TPA) or silver nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…For instance, vegetation with extensive root structures was shown to improve E. coli retention in stormwater biofilters [13]. Filter media modified with either antimicrobial compounds [14,15] or adsorption enhancements [16,17] were found to improve faecal indicator microorganism attenuation rates. Intermittent wetting/drying operation is generally associated with poor removal performances due to decreased microbial adsorption and increased microbial desorption [7,8,17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, vegetation with extensive root structures was shown to improve E. coli retention in stormwater biofilters [13]. Filter media modified with either antimicrobial compounds [14,15] or adsorption enhancements [16,17] were found to improve faecal indicator microorganism attenuation rates. Intermittent wetting/drying operation is generally associated with poor removal performances due to decreased microbial adsorption and increased microbial desorption [7,8,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies on bacteria removal in a wide range of structural BMPs concluded that bacteria treatment was ineffective and unreliable, as the removal of pathogens primarily relied on attachment/collection and not inactivation [13,14]. This is because sorbed pathogens can remain viable during attachment [15][16][17] and therefore can be remobilized/detached during intermittent flow conditions. The ineffectiveness in inactivating bacteria is especially relevant in areas with shallow water tables, because not enough soil depth might be present to filter out pathogens effectively, therefore increasing the risk of bacterial contamination of groundwater [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that filter materials amended with antimicrobials can remove bacteria from aqueous solutions by inactivation processes that damage the cell [15,16,27,28] or permanently fixating bacteria on porous media [16]. For instance, in a previous study antimicrobially amended wood chips were tested with intentions for use in stormwater BMPs [15,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations